Pengaruh Keputusan Investasi, Keputusan Pendanaan Dan Kebijakan Deviden Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015-2019) - Shellyana Ayu Kusuma Hapsari; Hadi Samanto; Muhammad Hasan Ma'ruf (Jurnal Akuntansi dan Pajak, 2021)
This study aims to see the effect of investment decisions, dividend decisions and policies on firm value. In this study, company value is measured by PBV, investment decisions as measured by PER, decisions measured by DER and dividend policy as measured by the DPR. This type of research is secondary data from annual reports of manufacturing companies listed on the Jakarta Stock Exchange, and has been published, such as: data from the Indonesia Stock Exchange (IDX), journals, internet www.idx.co.id and related company websites. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019, with the total number of food and beverage manufacturing companies listed on the Indonesia Stock Exchange as many as 14 companies, so for sample selection all populations were sampled. The analytical method used is multiple linear analysis using SPSS.22 data processing. The results of this study are the effect of positive decisions on firm value, no influence on decisions on firm value, no influence on dividend policy on firm value and investment decisions, funding decisions and policies that simultaneously do not affect firm value.